2021
DOI: 10.3390/molecules26164739
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiplasmodial Activity of Bisindolylcyclobutenediones

Abstract: Malaria is one of the most dangerous infectious diseases. Because the causative Plasmodium parasites have developed resistances against virtually all established antimalarial drugs, novel antiplasmodial agents are required. In order to target plasmodial kinases, novel N-unsubstituted bisindolylcyclobutenediones were designed as analogs to the kinase inhibitory bisindolylmaleimides. Molecular docking experiments produced favorable poses of the unsubstituted bisindolylcyclobutenedione in the ATP binding pocket o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Matthews (2015) stated that quinaprilat is the most effective compound inhibiting P. falciparum. Lande et al (2021) also discovered that the compound 3,4bis-cyclobut-3-ene-1,2-dione inhibit protein kinase plasmodial, which had a significant impact on the parasite malaria's life cycle (Arendse et al 2021). The findings of this study demonstrated that aqueous bidara laut heartwood extract from the maceration and UAE extraction methods could dissolve antimalarial alkaloid compounds.…”
Section: Phytochemical Profilementioning
confidence: 71%
“…Matthews (2015) stated that quinaprilat is the most effective compound inhibiting P. falciparum. Lande et al (2021) also discovered that the compound 3,4bis-cyclobut-3-ene-1,2-dione inhibit protein kinase plasmodial, which had a significant impact on the parasite malaria's life cycle (Arendse et al 2021). The findings of this study demonstrated that aqueous bidara laut heartwood extract from the maceration and UAE extraction methods could dissolve antimalarial alkaloid compounds.…”
Section: Phytochemical Profilementioning
confidence: 71%
“…Most derivatives showed submicromolar activity, and some displayed some selectivity against the human cell line THP-1. The most active compounds did not inhibit the plasmodial protein kinase PfGSK-3, so further studies are required to elucidate the mechanism of action of these compounds and to design derivatives with optimized aqueous solubility [ 71 ].…”
Section: Recent Development Of Indole-based Small Molecules Targeting Malaria Trypanosomiasis and Leishmaniasismentioning
confidence: 99%
“…In previous studies, PfGSK3β was considered as likely essential in asexual stages of the parasite and investigated as a potential drug target for the development of antimalarial kinase inhibitors ( 10 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ).…”
mentioning
confidence: 99%